RISKS OF CARDIOVASCULAR COMPLICATIONS IN PATIENTS WITH TYPE 2 DIABETES MELLITUS (BY THE EXAMPLE OF POLYCLINICS IN ALMATY) - M. S. Moldobaeva; M. O. Barmenbaeva; M. V. Krasnitskaya (Juvenis Scientia, 2022)
Introduction. In diabetes mellitus, uncontrolled hyperglycemia and a combination of risk factors (RF) of cardiovascular complications (CVC) are the causes of fatal cardiovascular events. Achieving target levels of glycemia, blood pressure, lipid profile, and weight loss has been shown to slow or stabilize CVC. Patients and Methods. We examined 398 patients with type 2 diabetes in outpatient clinics of Almaty city according to conventional criteria of carbohydrate and fat metabolism disorders, arterial hypertension (AH) and detection of nephropathy. Depending on the duration of diabetes mellitus, patients were divided into 4 groups. Risk groups of CVC were identified according to ESC / EASD (2019) and ESC / EACPR (2016) categories.. Results. All examined patients did not reach (glycated hemoglobin 8.18–8.7 %, LDL cholesterol 3.24–3.79 mmol / l, triglycerides 1.94–2.24 mmol / l, blood pressure 138.7–150.6 / 84.4–91.9 mm Hg) target levels of carbohydrate (glycated hemoglobin <7–7.5 %), fat metabolism (LDL cholesterol < 1.4 mmol / l, triglycerides < 1.7 mmol / l), blood pressure (BP 120–130 / 70–80 mm Hg). They also had signs of nephropathy (daily albuminuria 208–1080 mg / d, GFR (CKD-EPI) 50.6–80.6 ml / min), which were more pronounced with increasing duration of DM. Conclusion. The patients with type 2 diabetes in polyclinics of Almaty city have very high category of cardiovascular risk in all groups due to the following RF: dyslipidemia (100 %), AH (from 18.1 % to 31.8 % depending on the duration of diabetes), excessive body weight (100 %), as well as target organ damage such as diabetic nephropathy (from 13.8 % to 52.1 % depending on the duration of diabetes). Primary care physicians inevitably meet with patients with type 2 diabetes mellitus, so it is important to start combating the individual risks of CVC already in this area of health care.